2022
DOI: 10.1101/2022.03.02.22271731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vaccine Breakthrough Infection with the SARS-CoV-2 Delta or Omicron (BA.1) Variant Leads to Distinct Profiles of Neutralizing Antibody Responses

Abstract: There is increasing evidence that the risk of SARS-CoV-2 infection among vaccinated individuals is variant-specific, suggesting that protective immunity against SARS-CoV-2 may differ by variant. We enrolled vaccinated (n = 39) and unvaccinated (n = 11) individuals with acute, symptomatic SARS-CoV-2 Delta or Omicron infection and performed SARS-CoV-2 viral load quantification, whole-genome sequencing, and variant-specific antibody characterization at the time of acute illness and convalescence. Viral load at th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 30 publications
5
35
0
Order By: Relevance
“…This is in line with other studies where an omicron variant re-infection not only increased neutralizing antibody titers against omicron but also against other variants. 26,27 Surprisingly, we found that a delta variant breakthrough infection induced high titers against both omicron sub-lineages, although these individuals were never exposed to the omicron variant. In these individuals, neutralizing antibody titers against both omicron sub-variants were comparable to individuals who had a combination of prior infection/vaccination and omicron infection.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This is in line with other studies where an omicron variant re-infection not only increased neutralizing antibody titers against omicron but also against other variants. 26,27 Surprisingly, we found that a delta variant breakthrough infection induced high titers against both omicron sub-lineages, although these individuals were never exposed to the omicron variant. In these individuals, neutralizing antibody titers against both omicron sub-variants were comparable to individuals who had a combination of prior infection/vaccination and omicron infection.…”
Section: Discussionmentioning
confidence: 71%
“…However, others also found improved levels and durability of cross-neutralizing antibodies after three or more exposures (vaccination or infection). 3,8,27 In a non-human primate model, titers of cross-neutralizing antibodies were similarly increased by either a third dose of a wild type-specific mRNA vaccine or a beta-specific mRNA vaccine after two doses of a wild type-specific mRNA vaccine. 28…”
Section: Discussionmentioning
confidence: 98%
“…Understanding the role of antigenic imprinting in shaping the B cell response to antigenically drifted SARS-CoV-2 variants will be critical for the development of next-generation COVID-19 vaccines. Previous studies have shown that breakthrough infection with Delta or Omicron boosts serum neutralizing activity against both the Wuhan-1 vaccine strain and the infecting variant, suggesting recall of cross-reactive vaccine-induced MBCs ( 1214 ). However, the specificities, functions, and genetic features of the antibodies mediating this response remain poorly defined.…”
Section: Main Textmentioning
confidence: 99%
“…Understanding the role of antigenic imprinting in shaping the B cell response to antigenically drifted SARS-CoV-2 variants will be critical for the development of next-generation COVID-19 vaccines. Previous studies have shown that Delta or Omicron breakthrough infection boosts serum neutralizing activity against both the Wuhan-1 vaccine strain and the infecting variant, potentially suggesting recall of cross-reactive vaccine-induced MBCs ( 12 14 ). However, the specificities, functions, and genetic features of the antibodies mediating this response remain poorly defined.…”
Section: Introductionmentioning
confidence: 99%